The Loss of Raw Material Criticality: Implications of the Collapse of Saudi Arabian Oil Exports - Ulrich Blum; Jiarui Zhong (Intereconomics)
Abstract Raw material criticality has played an important role in geostrategic thinking, especially since the crisis surrounding the price and supply of rare earths at the beginning of the 2010s. However, once dependency and strategic importance grow too strong, substitution efforts will take place that could reduce or even eradicate the previous criticality. Critical resources rarely become obsolete very quickly. However, this could happen in the case of crude oil because climate policy is forcing defossilisation, but also because artificial scarcity is falling as a result of geostrategic rivalries that are causing oversupply. This article analyses this process and the possible consequences using Saudi Arabia as an example. The development of a green hydrogen industry has potential, but it should not be overestimated in view of the absorption capacity of the economy.